Analysis of prescriptions of substances subject to special control and antimicrobials in a community pharmacy in Campo Grande/RN (Research, Society and Development, 2020)
This observational and cross-sectional study aimed to analyze the prescriptions of drugs subject to notification or special control of community pharmacy located in Campo Grande/RN city. Was included prescriptions for medicines dispensed between February and April 2020, framed in Ordinance 344/1998 (psychotropic) and RDC 20/2011 (antimicrobial). The analysis was made using a form observing criteria such as identification, readability, address, dosage, route of administration, and pharmaceutical form. The main drug classes prescribed by the prescriber's specialty, as well as the most common substances, were also evaluated. Age, pharmaceutical form and route of administration were in this order the main inconsistencies found, especially in the prescriptions of special control type C. The specialty general practitioners represented 86.1% of the prescriptions, prescribing, mostly, drugs listed in the category of type C prescription, such as amitriptyline and escitalopram, these being the most prescribed drugs. However, in the group encompassed by notification type B, clonazepam was the main asset, corresponding to more than 50% of the revenue’s ac rented. Azithromycin was the most prescribed antimicrobial, with 22.95%. The findings showed that the professionals do not strictly follow the current technical standards, since the number of errors found in the prescriptions linked to the fact that they were aired generate a worldwide public health problem: the irrational use of medicines.